A interação da criança surda no contexto da educação infantil : um estudo de caso na perspectiva da educação inclusiva - Cigognini, Fabiane Lima (2021)
The relationships established in the school space are essential for the development of all children, including those who are in the process of inclusion, such as the deaf. In order to contribute to the understanding of this theme, this dissertation established as its main objective, from a case study, to investigate how the interactions between the deaf child and the hearing interlocutors happen in regular school. The research was justified by the need to expand knowledge about school inclusion - especially of children who attend Early Childhood Education in schools in the city of Passo Fundo - and to look at the teaching and learning process that take place in the encounter between deaf and hearing people.The study was based on theoretical principles in the area of deaf education that emerge from productions by Góes (2012), Goldfeld (2002), Quadros (2017) and Strobel (2016). It was presented a theoretical contribution that reiterates the relevance of the concepts of interaction, inclusion, development and learning, leading to the understanding of deafness as a linguistic difference. The first session provides an overview of Brazilian legislation on public policies aimed at inclusive educational actions that Brazil is a signatory and documents that directly impact the education of deaf people in regular schools.The second discusses the pedagogical approaches and practices in deaf education that allow us to understand how the views on these subjects were constituted throughout history. Finally, the third addresses considerations about the importance of early language acquisition in social interactions and for the development of deaf children, emphasizing the role that sign language plays in this process. It was opted an observation/transcription of recorded video material as a strategy for data generation. From the analysis of this material, it was identified the use of different communication resources/strategies, essential for the understanding of the student involved in the research, such as the exchange of looks and observation, approximation and affective touch, indicative gestures/notes, body language and expressions, as well as imitation and peer selection to establish relationships. We found that when these resources were not used, or when the interactions between the deaf student and her hearing interlocutors happened only through oral language, the relationships were marked by communication difficulties. Given this difficulty, we discussed essential indicators to boost the quality of interactions, such as: favorable linguistic conditions, the implementation of inclusion policies, the accessibility of communication and pedagogical practices that correspond to the way of being of deaf people in the world. We understand that “being together” cannot be considered an argument that supports inclusive education policies. In short, in the case of deaf students included in hearing classes, the fact that most of the time they do not have a structured language so that communication is established in a fluent way, and that they do not have deaf colleagues to share daily experiences, that the bases for inclusion are established from the principles of normalization and correction.